PENGARUH BAGI HASIL, SIZE, FDR, DAN BI 7-DAY REPO RATE TERHADAP PENGHIMPUNAN DANA PIHAK KETIGA BANK UMUM SYARIAH DI INDONESIA PERIODE 2014-2019 - Farida Musrifah; Mariana Mariana (Jurnal Bina Akuntansi, 2022)
The purpose of this research is to determine the effects from profit sharing, bank size, FDR, and Bi 7-Day Repo Rate on the collection of thirdparty funds at islamic commercial banks in Indonesia period 2014-2019. The method of analysis used in this research is Multiple Linear Regression model. The sample of this research was 12 islamic commercial Bank in Indonesia period 2014-2019. The result showed that simultaneously these four variables, namely: profit sharing, bank size, FDR, and Bi 7-Day Repo Rate had effect on the collection of thirdparty fundsat Islamic commercial banks in Indonesia in 2014-2019. While partially the profit sharing has a positive and significant effect on third party funds, the bank size has a positive and significant effect on third party funds, the FDRhas a negative and significant effect on third party funds, and Bi 7-Day Repo Rate doesn’t effect on third party funds